The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/1471-2458-10-338
|View full text |Cite
|
Sign up to set email alerts
|

Population based absolute and relative survival to 1 year of people with diabetes following a myocardial infarction: A cohort study using hospital admissions data

Abstract: BackgroundPeople with diabetes who experience an acute myocardial infarction (AMI) have a higher risk of death and recurrence of AMI. This study was commissioned by the Department for Transport to develop survival tables for people with diabetes following an AMI in order to inform vehicle licensing.MethodsA cohort study using data obtained from national hospital admission datasets for England and Wales was carried out selecting all patients attending hospital with an MI for 2003-2006 (inclusion criteria: aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…This could result in death caused by heart failure or sudden death because of an arrhythmia in patients with established CAD (30). Prior studies found that in patients with a myocardial infarction or a percutaneous coronary intervention, diabetes increases the risk of recurrent MCVE 1.5 to 2.0 times (31)(32)(33). These studies assessed the recurrence of myocardial infarction or death but not a composite of vascular events as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This could result in death caused by heart failure or sudden death because of an arrhythmia in patients with established CAD (30). Prior studies found that in patients with a myocardial infarction or a percutaneous coronary intervention, diabetes increases the risk of recurrent MCVE 1.5 to 2.0 times (31)(32)(33). These studies assessed the recurrence of myocardial infarction or death but not a composite of vascular events as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes was confirmed to be a strong risk factor for recurrence for both men and women and for all age groups. 15,16,34 Because of the limited information available in the dataset used for this study, the effect of the main coronary risk factors (smoking status, high blood cholesterol levels, and high blood pressure), which have been shown to affect AMI recurrence, 15 could not be assessed. Other factors that may have influenced recurrence, but could not be investigated in this study, include infarct severity, pharmaceutical treatment, psychological factors, social environment, and patient compliance with drug therapy and advice on physical activity, weight control, and healthy diet.…”
Section: Risk Of a Second Amimentioning
confidence: 99%
“…36 Linked Scottish Morbidity Record Database and Patient Episode Database for Wales, equivalents of the English HES, were reported to have high accuracy rates for the diagnosis of AMI. 16,37 Further limitations include the absence of clinical information, making it impossible to adjust for coronary risk factors and infarct severity, or to report on the diagnostic criteria used in making the clinical diagnosis of AMI. HES records do not contain information on drug prescriptions and thus treatment effect could not be examined.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that patients with diabetes mellitus have an increased risk of mortality and morbidity from cardiovascular disease compared to the general population [1,2,3,4,5,6,7,8,9,10]. A number of studies have also been published evaluating the impact of different regimens on the excess mortality observed [11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%